Karakterisasi Bahan Pewarna Tinta Termokromik Leuco Dye System Pada Produk Pempek Ikan - Susanti Thamrin, Elfa; Warsiki, Endang; Bindar, Yazid; Amalia Kartika, Ika (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 4 (2022): Jurnal ITEPA, 2022)
Good product packaging is one of the fundamental factors in determining the quality of a product. Along with the development of science and technology, modern packaging has evolved into intelligent packaging, which can directly communicate with consumers about the quality and quality of the packaged products without opening the package. One of the smart packaging trends being developed is thermochromic ink, or thermochromic ink that can be applied in the form of films or packaging labels. Thermochromic inks change color as processing and storage temperatures change. Smart packaging in the form of thermochromic ink (Thermochromic ink) uses one of the ingredients, namely the leuco dye system. The leuco dye system consists of 3 main components, namely dye, developer and solvent. Limitations in manufacturing thermochromic ink are that the dyes and developer materials used are toxic, which can pose a risk to human health when these materials migrate from packaging to packaged food products. Therefore, it is necessary to characterize the dye (dye) against temperature and pH changes. The purpose of this study was to characterize the dye used to produce thermochromic ink with the best color change. Characterization of dyes using pH indicator dyes include Bromothymol Blue, Bromophenol Blue, Bromocresol Purple, Bromocresol Green , and Methyl Red . 15 mg of pH indicator of each dye was dissolved in 10 ml of 97% ethanol and then immobilized on filter paper at room temperature for 24 hours. Test the indicator dye's sensitivity to NH 3 vapor by simulating NH3 vapor from NH4OH evaporating in a closed, airtight container. 10 mL of 1N NH 4 OH solution and 5 mL of each dye solution were placed in the same closed glass container. The variables observed were color changes and pH changes at 0, 5, 10 and 15 minutes.